Midlife and current physical activity is associated with functional brain connectivity in older age. (20th December 2022) - Ai, Meishan; Morris, Timothy Peter; Thovinakere, Nagashree; de la Colina, Adrián Noriega; Tremblay‐Mercier, Jennifer; Villeneuve, Sylvia; Kramer, Arthur; Geddes, Maiya R.; ,
Abstract: Background: Previous studies have shown a physically active lifestyle in both midlife and later life to benefit cognition and brain health in older age. However, exploring the influence of physical activity engagement on functional brain connectivity is needed to fully understand the neural mechanism underlying the effect of physical engagement. Additionally, in order to give lifestyle advice to different age groups, it is important to understand the unique contributions of physical activity at different life stages, which has rarely been examined. Method: The current study investigated the effect of self‐reported midlife and current physical activity engagement on functional connectivity among 105 cognitively high functioning older adults (age = 66.6±4.1). Self‐reported midlife and current moderate‐to‐vigorous physical activity (MVPA) were recorded using the Lifetime Total Physical Activity Questionnaire. We included covariates in all analyses (i.e., age, sex, years of education, socioeconomic status, genetic risk of Alzheimer's disease (i.e., APOE ε4 carrier status). Five regions of interest (ROIs) were selected based on previous literature on the relationship between exercise and brain health which included: prefrontal (i.e., bilateral superior frontal, middle frontal, and pars opercularis of the inferior frontal gyrus), and bilateral hippocampus. Result: Results showed that people who were active in midlife had greater functional connectivity between middle frontal gyrus and superior parietal region, postcentral gyrus (Voxel p <0.005, Cluster p <0.05 FDR corrected; figure 1a) than people who were relatively inactive in midlife. This effect stayed the same after controlling for current MVPA time. Secondly, the results showed that people who were active currently have greater functional connectivity between hippocampus and frontal pole (Voxel p <0.005, Cluster p <0.05 FDR corrected; figure 1b). Currently active participants also showed greater functional connectivity between pars triangularis of the inferior frontal gyrus, and bilateral middle temporal region, and frontal pole (Voxel p <0.001, Cluster p <0.05 FDR corrected; figure1c) compared to currently inactive participants, which stayed consistent after controlling for midlife MVPA time. Conclusion: As a conclusion, although midlife and current MVPA time were positively associated with each other, they both influence brain functional connectivity in later life independently. The results emphasize the importance of keeping a physically active lifestyle across midlife and into later life.